Biomimetic Direct Aldol Reaction of Pyruvate Esters with Chiral Aldehydes. Issue 2 (16th January 2013) - El‐Sepelgy, Osama; Mlynarski, Jacek
Abstract Direct aldol reactions of pyruvate esters with sugar aldehydes is efficiently promoted by dinuclear metal complexes or chiral Cinchona alkaloid organocatalysts. Application of sterically hindered aryl esters enables the to‐date problematic aldol reaction of pyruvate donors with syn‐ or anti‐selectivity en route to the short and efficient synthesis of 3‐deoxy‐2‐ulosonic acids.